أحكام الهجرة و التجنس في الفقه الإسلامي -دراسة فقهية مقارنة - - أحمد, عفيصة (University of Eloued جامعة الوادي, 2019)
"تتحدث هذا الدراسة المعنونة بي –أحكام الهجرة و التجانس في الفقه الإسلامي دراسة فقهية مقارنة عن إشكال رئيس هو : ما هو الهجرة إلى بلاد غير مسلمين في الحالة العادية "" السلم "" و الحكم الإقامة بها و التجنس ؟ تناولت ذلك في مبحثين خصصت الأول للتعريف بالهجرة ، ثم لأحكامها ،حيث تحصلت على رأيين أحدهما : يقول بالمنع و الآخر يقول بالجواز ،و كان الترجيح للثاني للاعتبارات قوية . ثم درست في المبحث الثاني قضية التجنس و ذلك بعد التعريف به ،ووصلت إلى رأيين متناقضين : أحدهما المنع و ثاني الجواز بشروط . خلصت الدراسة في الأخير إلى نتائج لعل من أهمها أن لموضوعي الهجرة و التجنس أحكاما مختلفة ،تتردد بين الوجوب و ذلك عند الضرورة الملجئة ،و بين التحريم دون مصلحة دينية ولا دنيوية ، و على ذلك فأحكامهما تتسم بالتفصيل المناسب للحالة كل فرد أو مجموعته ،و هي التوصية التي أشرت فيها إلى ضرورة التثبت و التمعن خاصة عند الإفتاء فيهما بصيغة العموم و مطالبة بمزيد من بحث " " This study, entitled ""Immigration and Naturailization Provisions in Islamic Jurisprudence,at a Comparative Jurisprudential Study"" on the issue of question of the rule: of the im migration to non-Muslim countries in the normal situation of ""peace"" and the rule of residence and naturalization? I dealt with this in two reseachs the first assigned to the definition of immigration, and then to its provisions, where It obtained two views: one says prevention and the other says the permissibility, and the weighting of the second permissible for stong considerations . Then I studied in the second research the issue of naturalization after the definition of it, and came two contradictory views: one prohibition and the other conditional. Finally This study concludes with the results of the most important of which is that the subjects of immigration and naturalization have different provisions, which differ between the obligatory and the obligatory necessity, and the prohibition is without religious and non-secular interest . Therefore, their provisions are detailed in detail of each individual or group. The recommendation in which I mentioned the need to be checked and especially in the FATWA in the form of the general and demand further research in them. "
مذكرة ماستر تخصص فقه وقانون
Keywords: الهجرة ، التجنس ، الجنسية ، إقامة; Immigration, naturalization, nationality, residence